2012
DOI: 10.1016/j.bmc.2012.02.001
|View full text |Cite
|
Sign up to set email alerts
|

Aglycone-focused randomization of 2-difluoromethylphenyl-type sialoside suicide substrates for neuraminidases

Abstract: A selective and potent inhibitor of neuraminidases, a hydrolase that is responsible for processing sialylated glycoconjugates, is a promising drug candidate for various infective diseases. The current study demonstrates that the use of an aglycone-focused library of 2-difluoromethylphenyl -sialosides is an effective technique to find potent and selective mechanism-based labeling reagents for neuraminidases. The focused library was constructed from a 4-azide-2-difluoromethylphenyl sialoside (2) and an alkyne-t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 31 publications
0
18
0
Order By: Relevance
“…Kai et al tested a 2-diuoromethylphenyl sialoside (12) against NEU2. 64 They conrmed that the compound could inactivate the enzyme in vitro and used an azide tag to generate a library of potential inhibitors. The most active compound identied had a reported inhibition constant of 200 mM.…”
Section: Substrate Recognition In Hneumentioning
confidence: 99%
“…Kai et al tested a 2-diuoromethylphenyl sialoside (12) against NEU2. 64 They conrmed that the compound could inactivate the enzyme in vitro and used an azide tag to generate a library of potential inhibitors. The most active compound identied had a reported inhibition constant of 200 mM.…”
Section: Substrate Recognition In Hneumentioning
confidence: 99%
“…A perusal of the literature revealed that pyrimidine derivatives and the uracil and thymine nitrogen bases [ 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 ] are efficient inhibitors to protect steel in acidic solutions [ 15 , 17 ]. 1,2,3-Triazoles have been the subject of considerable research, mainly due to their usefulness in synthetic organic chemistry and also due to their variety of interesting biological activities, forming part of the scaffolds of antibacterial and antituberculosis agents [ 18 , 19 ], neuraminidase inhibitors [ 20 ], anticancer compounds [ 21 , 22 , 23 , 24 ], antiviral agents [ 25 , 26 , 27 ], analgesic compounds [ 28 ], fungicidal activity [ 29 , 30 , 31 ], protein tyrosine phosphatase inhibitors [ 32 , 33 ], and assorted biomolecules (nucleosides and nucleotides) [ 34 , 35 ]. On the other hand, 1,2,3-triazoles have other applications, like in chemosensors [ 36 ] and organocatalysts [ 37 ].…”
Section: Introductionmentioning
confidence: 99%
“…Treatment of 6 with 1,1′‐thiocarbonyldiimidazole in tetrahydrofuran (THF) under reflux afforded 1‐(4‐cyclopropylnaphthalen‐1‐yl)‐1H‐imidazo[4,5‐b]pyridine‐2‐thiol ( 7 ) . The final imidazo[4,5‐b]pyridin‐2‐ylthioacetanilides 8 – 25 were obtained by reaction of 7 with a set of 2‐chloro‐ N ‐aryl‐substituted acetamides or propanamides in a rapid and convenient way . Both analytical and spectral data of all the newly synthesized compounds are in full agreement with the proposed structures.…”
Section: Resultsmentioning
confidence: 99%
“…The metal-catalyzed cross-coupling reaction of 4 with already prepared intermediate 2 afforded N-(4-cyclopropylnaphthalen-1-yl)-2-nitropyridin-3-amine (5) c . Then, the nitro group of intermediate 5 was treated with excess hydrogen gas in the presence of hydrogenation-catalyzed Pd/C (20%) to afford N 3 -(4-cyclopropylnaphthalen-1-yl)pyridine-2,3-diamine (6) were obtained by reaction of 7 with a set of 2-chloro-Naryl-substituted acetamides or propanamides in a rapid and convenient way (41,42). Both analytical and spectral data of all the newly synthesized compounds are in full agreement with the proposed structures.…”
Section: Chemistrymentioning
confidence: 99%